THE CRIMES COMMITED BY CHILDREN AND THE PENAL POLICY OF THE COURTS TOWARDS CHILDREN IN THE REPUBLIC OF NORTH MACEDONIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The authors of the paper refer to the criminological aspects of the criminality of children in the Republic of North Macedonia, as well as, to the penal policy of the courts towards children. The criminality of children in a certain society is the best, most reliable indicator of the position of the young generation in that society and what is the attitude of that society towards them. In the criminological literature, there is a thesis that the criminality of children is always behind the profound changes in the phenomenological characteristics of the criminality, because “a child offender today is a recidivist tomorrow”. When it comes to the penal policy that should be conducted towards children, the international norms and standards, as well as, the solutions of the European legislation incorporated in the Law of Justice for Children, emphasize educational measures instead of retributive punishments, as well as, the increased engagement of centers for social assistance, and pedagogical and social professional treatment. The system of sanctions in the Republic of North Macedonia provided for children emphasizes the preventive, educational, protective, educational and corrective function of the sanctions, while emphasizing the exclusive application of the prison sentence only for older minors and for the most serious crimes committed. On the other hand, the fact that the most serious forms of crime committed by children, with elements of violence, aggression, committed in gangs, etc., are registered is worrying. The criminality of children is gaining importance due to its close connection with sociopathological phenomena, and the age limit for criminality of children and the sociopathological phenomena that go along with it (alcoholism, drug addiction, prostitution, sexual deviations, vagrancy, etc.) is getting lower and lower. Hence, there is a need to review the minimal age of criminal responsibility of children in our country.
Keywords: criminality of children, sanctions for children, educational measures, prison for children, criminal responsibility of children, retribution, upbringing, sociopathological phenomena.